PERILLA FRUTESCENS – A REVIEW ON PHARMACOLOGICAL ACTIVITIES, EXTRACTION PROCEDURE AND APPLICATIONS - K, VANITA; T, MEGH; D, SHIVAM (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Perilla frutescens, a member of the mint family Lamiaceae, is a medicinal, aromatic, edible, and beautiful plant. The source of perilla lies into East Asian countries (China, Japan, Korea, Taiwan, Vietnam, and India), in which it is been used as an important root of culinary and conventional medicinal uses. Perilla plant’s leaves, seeds, and stems are utilized in community medicine for a variety of ailments [1]. Recently, Perilla plant is gaining extra interest due to its medicinal advantages and phytochemical contents. The fundamental phytochemical compounds found in this species are phenolic compounds (Rosmarinic acid, caffeic acid, and ferulic acid), flavonoids (luteolin and apigenin), Phytosterols, Tocopherols, Policosanols, and Fatty acid. Perilla seed oil too is a wealthy supply of vital fatty acid which includes α-linolenic acid (54–64%) and linoleic acid (14%) [2]. Perilla has shown different biologicalactions for example, antioxidant, antimicrobial, anti-allergic, antidepressant, anti-inflammatory, anticancer, and neuroprotective actions. Perilla seed oil consists of omega-3-fatty acid, and alpha-linolenic acid (ALA). In comparison to other plant oils, perilla seed oil has one of the highest percentages of omega-3 (ALA) fatty acids, at 54–64%. The omega-6 (linoleic acid) is around 14% and omega-9 (Oleic acid) too is found in perilla oil. These polyunsaturated fatty acids are very useful to human wellbeing and in prevention of various illnesses such as cardiovascular disorders, cancer, inflammatory, and rheumatoid arthritis [3].